Pelatihan Pembuatan Toko Online dengan Google Sites - Andri Andri; Somawati Somawati (Institut Teknologi dan Bisnis Semarang, 2024)
The marketing skills program covers the important topics of Digital Business. This program can be a great choice for individuals who want to build a successful career in today's industrial world, whether working for someone else, starting their own business, or pursuing further education that matches their interests. In addition, the course equips graduates with the necessary skills to pursue careers in various digital fields such as digital entrepreneurship, content writing, social media management, digital marketing, merchan, online customer service and purchasing. This will create an interactive and challenging learning environment that motivates students to participate actively and provides space for creativity, independence according to their talents, interests and psychology. Creating an online store can be done using various applications such as Blogs, e-commerce platforms or special websites built with google sites. As part of community service activities, students at SMK Wisata Indonesia Jakarta will receive comprehensive training in creating an online store using Google Sites. Google Sites is a service provided by Google that allows users to create websites without the need for coding skills or advanced web design. Google Sites is designed to be user-friendly and accessible to a wide variety of users. In conclusion, it is worth considering that creating an online store with Google Sites as a form of community service can foster entrepreneurial attitudes and improve digital business skills. Although the participants may require further development, especially in website development, it is important to note that this is just one aspect of building a successful website.